Thermospheric Temperature and Density Variability During 3–4 February 2022 Minor Geomagnetic Storm. Issue 4 (7th April 2023) - Laskar, F. I.; Sutton, E. K.; Lin, D.; Greer, K. R.; Aryal, S.; Cai, X.; Pedatella, N. M.; Eastes, R. W.; Wang, W.; Codrescu, M. V.; McClintock, W. E.
Abstract: Themospheric conditions during a minor geomagnetic event of 3 and 4 February 2022 has been investigated using disk temperature ( T disk ) observations from Global‐scale Observations of the Limb and Disk (GOLD) mission and model simulations. GOLD observed that the T disk increases by more than 60 K during the storm event when compared with pre‐storm quiet days. A comparison of the T disk with effective temperatures ( T eff, i.e., a weighted average based on airglow emission layer) from Mass Spectrometer Incoherent Scatter radar version 2 (MSIS2) and Multiscale Atmosphere‐Geospace Environment (MAGE) models shows that MAGE outperforms MSIS2 during this particular event. MAGE underestimates the T eff by about 2%, whereas MSIS2 underestimates it by 7%. As temperature enhancements lead to an expansion of the thermosphere and resulting density changes, the value of the temperature enhancement observed by GOLD can be utilized to find a GOLD equivalent MSIS2 (GOLD‐MSIS) simulation—from a set of MSIS2 runs obtained by varying geomagnetic ap index values. From the MSIS‐GOLD run we found that the thermospheric density enhancement varies with altitude from 15% (at 150) to 80% (at 500 km). Independent simulations from the MAGE model also show a comparable enhancement in neutral density. These results suggest that even a modest storm could impact the thermospheric densities significantly and GOLD data can be used to improve the empirical and assimilative models of the thermosphere. Plain Language Summary: High speed plasma from the sun can bring energy, momentum, and particles into the Earth's upper atmosphere triggering a geomagnetic storm, which disturbs the thermosphere‐ionosphere (TI) system. It is observed that even minor geomagnetic events can have a significant impact on the TI system. In this work we have investigated the neutral properties of the thermosphere during a minor geomagnetic event using NASA‐Global‐scale Observations of the Limb and Disk (GOLD) mission observations. By calibrating the Mass Spectrometer Incoherent Scatter radar version 2 empirical model based on the temperature change observed by GOLD, we have found that the thermospheric density increased by 15% (at 150) to 80% (at 500 km). These results demonstrates that the GOLD data can help in improving thermospheric empirical models. Also, they can help satellite‐drag and space weather forecasters to find ways to improve their products. Key Points: Global‐scale Observations of the Limb and Disk (GOLD) observed a ∼60 K rise in lower‐to‐middle thermospheric temperature during a minor geomagnetic storm on 3–4 February 2022 GOLD‐informed MSIS calculations indicate an increase in density by 15% (at 150) to 80% (500 km), which agrees with Multiscale Atmosphere‐Geospace Environment estimation GOLD T disk can be used in empirical and data assimilative forecasting models to improve thermospheric specifications